2020
DOI: 10.1016/j.cma.2019.112758
|View full text |Cite
|
Sign up to set email alerts
|

Bending models of lipid bilayer membranes: Spontaneous curvature and area-difference elasticity

Abstract: We preset a computational study of bending models for the curvature elasticity of lipid bilayer membranes that are relevant for simulations of vesicles and red blood cells. We compute bending energy and forces on triangulated meshes and evaluate and extend four well established schemes for their approximation: Kantor and Nelson [1], Jülicher [2], Gompper and Kroll [3] and Meyer et. al. [4], termed A, B, C, D. We present a comparative study of these four schemes on the minimal bending model and propose extensio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 64 publications
(168 reference statements)
9
77
0
Order By: Relevance
“…where κ is the bending rigidity andn i andn j are (consistently oriented) triangle normals 55,[57][58][59] . Note that such a model of bending may not be generally applicable for capturing bending forces of real materials (e.g., those that are nonlinear or plastically deform) or other models (e.g., the Helfrich-Canham model) at large curvatures.…”
Section: Model and Methodsmentioning
confidence: 99%
“…where κ is the bending rigidity andn i andn j are (consistently oriented) triangle normals 55,[57][58][59] . Note that such a model of bending may not be generally applicable for capturing bending forces of real materials (e.g., those that are nonlinear or plastically deform) or other models (e.g., the Helfrich-Canham model) at large curvatures.…”
Section: Model and Methodsmentioning
confidence: 99%
“…In the area difference elasticity model [ 40 , 43 ] a vesicle is considered as an elastic membrane and its equilibrium shape can be found with the minimization of the Helfrich energy [ 48 , 49 ] ( W ). In this model not just the local principal curvatures ( and ) can differ from their equilibrium value, i.e., from the local spontaneous curvature ( ), but an elastic membrane is taken into account, so the area difference between the inner and outer leaflets ( ) can be different from its equilibrium value (from the preferred area difference ) as well.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the urea–urease enzymatic reaction [ 32 , 33 , 34 ] inside the lumen of the vesicles, coupled to the cross-membrane transport of urea, can trigger the shape deformation of the pH-sensitive mixed membrane by promoting the solubilization of oleate molecules in the inner water phase. In the framework of the Area Difference Elasticity (ADE) theory [ 23 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] we demonstrated that the shape deformation is driven by the synergic action of osmosis, acting on the volume of the vesicle, and pH change, the latter responsible for the increase of the preferred area difference of the bilayer leaflets. However, the ADE model predicts that the equilibrium shape of an elastic membrane undergoing a transformation, also depends on a third factor: the mechanical properties of the bilayer accounted by the ratio of the local (intrinsic fluidity of the membrane) and the non-local (tension generated by the different curvature of the two leaflets) bending moduli.…”
Section: Introductionmentioning
confidence: 99%
“…The software Surface Evolver 2.70 42 was used to compute the relaxed vesicle shape by minimizing the energy functional W, i.e. the Helfrich energy, 43,44 complemented with a term that, according to the ADE theory, accounts for the area difference between the outer and inner leaflets of the lipid membrane, 45,46 expressed by…”
Section: Simulations Of the Deformation Of Vesiclesmentioning
confidence: 99%